Development of a valid and reliable scale to assess knowledge, attitude and practice (KAP) on frailty, nutrition and exercise among Malaysian elderly - Mohd Suffian, Nurul Izzati; Adznam, Siti Nur ‘Asyura; Abu Saad, Hazizi; Ibrahim, Zuriati; Omar, Noraida (Faculty of Medicine and Health Science, Universiti Putra Malaysia, 2023)
Introduction: “Frailty Intervention through Nutrition Education and Exercise (FINE)” program is an educational program, an initiative to ameliorate frailty status among elderly due to the alarming number of frailty cases in Malaysia. The current study aims to develop and determine the validity and reliability of the KAP questionnaire on frailty, nutrition and exercise to assess the effectiveness of the “FINE” program among the Malaysian elderly. Methods: The KAP questionnaire was created based on the developed frailty module and education materials. Content and face validity were conducted before the reliability study among five health professionals and 20 elderly, while 79 elderly were involved in a reliability study in three different Projek Perumahan Rakyat (PPR) flats in the Kuala Lumpur area. Data were analysed to determine its internal consistency reliability. Results: Six items were removed during content and face validity, two from each domain. All items in the knowledge section were within an acceptable range of difficulty and discrimination following the item analysis. Yet, item-to-total correlation removes one item for attitude and four items for the practice domain. The analysis found that the internal consistency reliability was 0.852, 0.732 and 0.600 for the KAP section, respectively. Conclusion: The final version of the KAP questionnaire consisted of (11) knowledge, nine (9) attitudes and six (6) practice items proven to be valid and reliable. Thus, it could be used to assess the effectiveness of the “FINE” program among the Malaysian elderly.